DETERMINANTS OF PROFESSIONAL CAREER CRISIS OF THE AGE OF MATURITY AND POSSIBILITIES FOR OVERCOME THEM - S. Grishaeva; E. Makarova (Вестник университета)
The features of building a career at a mature age are discussed in the article. The features of professional and age crisises, including the factors of the crisis of adulthood, the place for career ambitions in the process of entering and exiting the crisis, the possibilities of overcoming them are revealed. The role and essence of acmeological accompaniment of an employee in the period of pro-fessional crisis is revealed, a thorough analysis of psychological peculiarities of the age of maturity, potential possibilities of self-realization on different stages of a career is conducted.